DEEP SEDIMENTARY BASINS PROVED IN SHETLAND-HEBRIDEAN CONTINENTAL SHELF AND MARGIN - Bott, M; Watts, A (1970)
A REGIONAL geophysical survey of the continental shelf and margin west of the Orkney and Shetland Isles was completed during cruises of RRV John Murray in 1967 and 1968. These surveys yielded about 9,000 km of continuous surface ship gravimeter and magnetometer track across the shelf and margin, including ten seismic reflexion (sparker) traverses. This report gives a preliminary interpretation of the resulting Bouguer anomaly map (Fig. 1). © 1970 Nature Publishing Group.